Legal understanding of industrial observations in the field of environmental protection, rational (sustainable) use of natural resources in the implementation of economic and other activiti - Moroz, Oleg V. (Journal of the Belarusian State University. Law, 2024)
The author of the article reveals the legal understanding of industrial observations in the field of environmental protection, rational (sustainable) use of natural resources in the implementation of economic and other activities, including the comparison with the concept of industrial environmental control under the abolished legislation. It is proposed to expand the legal understanding of such industrial observations to control over compliance by legal entities and individual entrepreneurs with environmental legislation in general. According to the existing legal approach, they are primarily aimed at checking (assessing) the compliance of economic and other activities with the requirements in the field of environmental protection. In this regard, it is advisable to return to the term «industrial environmental control». The article provides a rationale for industrial observations as an element of environmental support for economic and other activities. Proposals are presented to improve the legal consolidation of the environmental protection measure under consideration.